2013
DOI: 10.1007/s00216-013-7075-y
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization imaging mass spectrometry revealed traces of dental problem associated with dental structure

Abstract: Periodontal disease is a serious dental problem because it does not heal naturally and leads to tooth loss. In periodontal disease, inflammation at periodontal tissue is thought as predominant, and its effect against tooth itself remains unclear. In this study, we applied matrix-assisted laser desorption/ionization imaging mass spectrometry (IMS) to teeth for the first time. By comparing anatomical structure of tooth affected with periodontal disease with normal ones, we analyzed traces of the disease on tooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Furthermore, for ionization, an electrically conducting double-adhesive tape is needed to affix sections on the ITO-glass slide (Hirano et al, 2014). Comparison of mass spectra between sections with or without tape revealed that many more peaks were obtained from the section without tape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, for ionization, an electrically conducting double-adhesive tape is needed to affix sections on the ITO-glass slide (Hirano et al, 2014). Comparison of mass spectra between sections with or without tape revealed that many more peaks were obtained from the section without tape.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are few studies that have applied MALDI-IMS to bone tissues to identify molecules because of the lack of appropriate methods to prepare sections for ionization (Hirano et al, 2014, Cillero-Pastor et al, 2015, Seeley et al, 2014). Hirano et al (Hirano et al, 2014) reported MALDI-IMS for tooth cryosections prepared by the Kawamoto method using adhesive film without any pretreatment, such as fixation or decalcification. However, the signals obtained from the enamel and dentin were not listed in the metabolomics database.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of head and neck cancer, the spatial molecular characterization is important, since half of the patients develop a locoregional recurrence although radical therapy was prescribed. 147 Besides, cancer applications, various other diseases, such as infections of hepatitis B virus, 81 atherosclerosis, 148 fabry, 79 peridontal, 149 alzheimer's, [150][151][152] epilepsia, 153 stroke, 154 schizophrenia, 155 and stargardt disease 82 have been investigated to shade light into the underlying disease mechanism. 50 With the help of computational algorithms, the head and neck tissue sample was subdivided into six clusters based on the spectral similarities (Figure 3 A).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Setou et al . recently performed MALDI-IMS upon teeth with periodontal disease and found that an accumulation and infiltration of LPC to the root surface were related to periodontal disease [59]. High-resolution (HR) MALDI-IMS is an emerging application for the comprehensive and detailed analysis of the spatial distribution of ionized molecules in situ on tissue slides, and 26 molecules as highly expressed were identified in prostate carcinoma by HR MALDI-IMS [60].…”
Section: The Ionization Technologies Of Msmentioning
confidence: 99%